Species richness of zooplankton in small lakes of Almaty region (Experimental biology, 2020)
Studies of small lakes are topical for awareness of their role in the conservation of biological diversity. A study of seven small lakes in the Almaty region (Malaya Podkova, Bolshaya Podkova, Kosagash, Derevyannoe, Altynkol, Ali, Pervomaika) was carried out in June and August 2019. Standard methods performed the sampling and processing of samples. Zooplankton was represented by 54 taxa. The minimum number of species of planktonic invertebrates was recorded in Lake Bolshaya Podkova, the maximum one in Pervomaika lake. Species A.priodonta, K. cochlearis, K. quadrata, A. rectangula, B. longirostris, T. crassus were widespread. There were no significant differences in the composition of zooplankton from the beginning to the end of summer in lakes Ali, Derevyannoe, Kosagash, Altinkol. However,  in the lakes Bolshaya Podkova, Malaya Podkova, and Pervomaika, the value decreased four times. A comparative analysis of the complex of widespread species of zooplankton revealed a significant similarity with those of water bodies, which are under the influence of planktivorous fish. The specific features of the zooplankton fauna of small lakes in the Almaty region are due to the combined impact of environmental factors, primarily the development of macrophytes, food resources, hydrochemical regime, and distribution of planktivorous fish.           Key words: small lakes, zooplankton, species richness.